The Effects of Activation Treatments for Crumb Rubber on the Compatibility and Mechanical Performance of Modified Asphalt Binder and Mixture by the Dry Method - Liang, Ming; Qiu, Zhengmei; Luan, Xuehao; Qi, Cong; Guo, Ning; Liu, Zhaoxin; Su, Linping; Yao, Zhanyong; Zhang, Jizhe (Frontiers in Materials, 2022)
Compatibility and mechanical performance of crumb rubber (CR)-modified asphalt and mixtures prepared by the dry method are poor at present, which limits the application of dry-mixed asphalt rubber in paving engineering. To solve this problem, various activated treatments for CR were performed, and the modified asphalt binder was prepared by the dry process in this study, aiming to activate the CR as the modifier and improve the compatibility of CR-asphalt blends. The effects of pre-treating methods of high temperature, pre-swelling, and microwave treatment on rutting resistance and compatibility of the asphalt binder and asphalt mixture were evaluated. Furthermore, the dynamic shear rheometer (DSR) of temperature sweep, Brookfield rotary viscosity, physical properties, rutting resistance, and microstructure of modified asphalt were measured. The results indicated that the three treatments have a pronounced effect on the high temperature performance of the crumb rubber-modified asphalt (CRMA) binder in the dry process and modified asphalt storage stability improvement. The high-temperature and microwave pre-treatment for CR lead to the largest complex modulus, viscosity, and rutting factor. Moreover, high-temperature, pre-swelling, and microwave treatment for CR significantly increases the dynamic stability of dry-mixed asphalt mixtures, which indicates the enhanced resistance to permanent deformation. In microscopy, homogeneous and compatible states were obtained for asphalt modified by high temperature-treated CR and pre-swelled CR, in which the strong interaction occurs among rubber molecules and the asphalt component. The microstructure of dry CR-asphalt blends sheds light on the mechanical performance. Consequently, activated CR modification for the asphalt binder by the dry process in this study is a promising technology, and other properties need to be verified in the future.